The Effect of Workload, Work Discipline, and Work Motivation on Employee Performance in the Legal and Cooperation Section of the Secretariat of the Directorate General of Sea Transportation - Qusay Al Rasyidi Hidayatullah; Setyani Dwi Lestari (CV. Creative Tugu Pena, 2025)
The Employee performance is an important factor in supporting the effectiveness of the implementation of tasks and functions within government organizations. Various human resource management factors are believed to influence employee performance, including workload, work discipline, and work motivation. This study aims to analyze the effect of workload, work discipline, and work motivation on employee performance in the Legal and Cooperation Division of the Secretariat of the Directorate General of Sea Transportation. This research employs a quantitative approach using a survey method. The population of this study consists of all employees in the Legal and Cooperation Division of the Secretariat of the Directorate General of Sea Transportation, with a total of 56 respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis. Prior to conducting the regression analysis, the data were first tested through validity tests, reliability tests, and classical assumption tests. The results of the study indicate that simultaneously, workload, work discipline, and work motivation have a significant effect on employee performance. Partially, work discipline and work motivation have a positive and significant effect on employee performance, while workload does not have a significant effect on employee performance. The coefficient of determination (R²) value of 0.308 indicates that workload, work discipline, and work motivation are able to explain 30.8% of the variation in employee performance, while the remaining variation is influenced by other factors outside the research model. Based on the findings, it can be concluded that improving employee performance in the Legal and Cooperation Division of the Secretariat of the Directorate General of Sea Transportation is more effectively achieved through strengthening work discipline and enhancing work motivation rather than merely adjusting workload. The results of this study are expected to serve as a consideration for leaders in formulating human resource management policies to improve employee performance sustainably.